2016
DOI: 10.1680/jmacr.15.00451
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and loading rate on the compressive behaviour of CA mortar

Abstract: The coupled effect of loading rate and temperature on the compressive behaviour of cement asphalt mortar (CA mortar) is investigated in this paper. The uniaxial compressive test is conducted with CA mortar subjected to three different temperatures from 5°C to 35°C and seven different loading rates in the range of 1–50 mm/min. The failure modes, experimental stress–strain relationship and compressive strength of CA mortar are obtained in this study. Based on the experimental results, it is found that CA mortar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In addition, the prestressed tendons of the track slab were tensioned at 7 d, and the ambient relative humidity in the shrinkage and creep model was 70%. The initial relative humidity of CA mortar is 100%, and the average strength is 11.35 MPa [ 49 ].…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…In addition, the prestressed tendons of the track slab were tensioned at 7 d, and the ambient relative humidity in the shrinkage and creep model was 70%. The initial relative humidity of CA mortar is 100%, and the average strength is 11.35 MPa [ 49 ].…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…e compressive strength, tensile strength, dynamical modulus, and stress-strain response of CAM with different asphalt to cement ratio were experimentally studied when the temperature was varied. e experimental results indicated that (1) the mechanical properties of CAM decreased with the increasing temperature [2,9], (2) the temperature sensitivity of CAM was closely related to the asphalt to cement ratio [11,12], and (3) the temperature-sensitive behavior of CAM was also found to be correlated with the loading rate and water pressure [13][14][15]. According to the research, the behavior of CAM under low and high temperature can be well interpreted and reasonably predicted by the proposed model.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate how track slab damages initiate and how they affect vehicle-track system dynamics and track irregularities, previous studies carried out numerical simulations [3][4][5][6][7][8][10][11][12][13][14][15][16], full-scale tests [9,[17][18][19], and field tests [15,20,21]. These studies shed some light on repair works for defects, slab maintenance, and life-cycle management of slab track.…”
Section: Introductionmentioning
confidence: 99%